Uzbek Jadid Thinker Abdulla Avloni's Viewpoints On Concerning Relationship Between Man And Nature - Akramjon Bakhromovich Gulomov (International Scientific and Current Research Conferences, 2020)
The article analyzes Abdulla Avloni's views on the aesthetic attitude of a person to nature, its correlation and integration with the environmental consciousness and culture of society, development of eco-aesthetic communication of nature with Man, optimization of interests and needs, formation of aesthetic attitude of a person to nature and interaction between the levels of development of environmental consciousness.